THE EVOLUTION OF SARS-COV-2, A REVIEW OF GENETIC MUTATION - Mohammed, Ghaith R (International Journal of Research -GRANTHAALAYAH, 2024)
SARS-CoV-2 emerged from zoonotic coronaviruses and is a novel beta-coronavirus which causes severe respiratory disease (pneumonia and lung failure), termed COVID-19. This paper describes SARS-CoV-2 genetic features (mutations and molecular epidemiology) but highlights its key differences from animal coronaviruses. We conducted a synthesis of the knowledge regarding clinical, genetic and pathological features of animal coronaviruses in comparison to SARS-CoV-2, along with recent evidence of interspecies transmission and recombination of animal coronaviruses to inform a One Health perspective of SARS-CoV-2 infection. We also take a closer look at the likely animal reservoirs and zoonotic origins of this novel virus that could help to curb disease transmission and minimize disease impact.